Price and output effects of Monetary policy in Low Income Countries: The Case of Nepal - Dhakal, Nanda Kumar; Timsina, Mitra Prasad (Advances in Social Sciences Research Journal, 2020)
This paper examines the impact of monetary policy on economic growth and inflation in Nepal. The impact on economic growth and inflation have been observed using monetary policy instruments/indicators such as CRR, bank rate, interbank rate, M1, M2, private sector credit based on quarterly data from first quarter of 2006 to fourth quarter of 2018. The impact on economic growth and inflation rate has been examined separately. The econometric methods like ADF test, ARDL Model, Bound Test, Error Correction Model, Residual Test and Stability test have been used in the study. The empirical results show that economic growth and inflation are influenced by monetary policy. CRR, bank rate, broad money and private sector credit are significant to have impact on economic growth. Likewise, money supply (M1 and M2) has impact on inflation. The result shows that it takes longer time to have impact of broad money and private sector credit on economic growth than on inflation.